Effects of eucalyptus leaves blending on combustion characteristics of an Indian reject coal. Issue 1 (31st March 2022) - Aich, Subhajit; Nandi, Barun Kumar; Bhattacharya, Sumantra
ABSTRACT: Presents work aims at the results obtained from experimental studies on utilization of eucalyptus leaves (ECL) to enhance the burning performance of a coal cleaning plant reject well known as reject coal (RC). Different parameters of combustion like; temperature of ignition (Ti ), peak temperature (Tp ), temperature of burnout (Tb ), peak combustion rate (DTGmax ), index of ignition (Di ), index of burnout (Df ), index of combustion performance (S), and index of rate intensity (Hf ) were obtained from TGA-DTG experiments to optimize the blending ratio of ECL and RC. Experimental results showed that there is improvement in combustion performance of RC when 20% by mass of ECL is blend with 80% by mass of RC and reducing Ti from 449℃ to 429℃, Tp from 511℃ to 509℃, and Tf from 567℃ to 552℃. Addition of higher quantities of ECL up to 90% mass, reduces Ti, Tp, Tb further down to 234℃, 476℃ and 508℃ respectively and increases DTGmax from 3.64 to 4.73 wt%/minute. Considering the various parameters of combustion, maximum of 20% mass of ECL having 78% volatile matter, 6985 kcal/kg GCV are recommended to blend with 80% by mass of RC having 11% volatile matter and 3105 kcal/kg GCV for thermal utilities. Experimental results confirmed that, ECL can be burned with coal to reduce the overall coal consumption, thus decreases the carbon footprint of coal fired utilities.